Comparison of Transoral and Transcervical Ultrasonography with MRI for the Diagnostic Work-Up of Oropharynx Tumors: A Protocol for a Multicenter Clinical Trial (SPOTUS) - Martin Garset-Zamani; Gitte Bjørn Hvilsom; Thomas Kjærgaard; Christina Caroline Plaschke; Christoffer Holst Hahn; Mikkel Kaltoft; Padraig O’Leary; Natalie Lassen Frid; Rikke Norling; Danijela Dejanovic; Johanna Maria Hall; Tina Klitmøller Agander; et al. (Diagnostics, 2024)
This study protocol for a prospective, multicenter, diagnostic, clinical trial describes the integration of transoral and transcervical ultrasonography (US) in the initial clinical work-up of patients referred to tertiary head and neck cancer centers with suspected oropharyngeal cancer. The study evaluates the blinded detection rate of oropharyngeal tumors and their US-estimated size and T-stage before histopathology and cross-sectional imaging are available. Magnetic resonance imaging (MRI) scans will be prospectively rated while blinded to T-site histopathology and US. The primary outcome measures of diagnostic accuracy, including sensitivity, specificity, positive and negative predictive values, and overall accuracy, will be reported for both US and MRI. A sub-analysis of prospectively rated 18F-Fluorodeoxyglucose (FDG) positron emission tomography/computerized tomography (PET/CT) scans in patients with clinically suspected unknown primary tumors will also be compared to US and MRI. Secondary outcome measures, including a comparison of tumor size estimation between US, MRI, and CT, will also be reported. This prospective multicenter study will provide clinically impactful information regarding the use of transoral and transcervical US for the diagnostic work-up of oropharyngeal cancer.